Evaluación técnica y sanitaria del sistema de camales municipales de la provincia de El Oro - Moran Sánchez, Sarita Isaurina (2014)
This investigation was performed in four cantons of El Oro province: Machala, Pasaje, Santa Rosa y Marcabeli. The principal goal was to contribute to the efficiency and effectiveness of the municipal meat processing plants in El Oro province by starting an evaluation of the sanitary conditions and productive techniques that would foster comprehensive improvement plans. The specific objectives were: 1.To assesses the status of health conditions and production technique from the 4 municipal meat processing plants in comparison to the protocol of good manufacturing practices. 2. To establish an improvement plan for each specific meat processing plant with the main focus of decentralizing the plant to function autonomous of government (municipal governments) .The idea for this method stemmed from discovering the unfortunate reality of the meat processing plants disorganized and subpar infrastructure, technical management and its impact to the plant’s environment. The method used techniques such as interviews and surveys, which led to the creation of a system that analyzed the data and identified suggestions and criticisms from all entities involved. Fifty-four surveys were distributed to contracted personnel, or personnel associated by appointment, in the municipalities. The results: Each meat processing plant had a different model in relation to the days and hours of employee’s work schedules. The cattle that were used were cows, pigs and goats. The meat processing plants that had the highest production processing of cattle was in the canton of Marcabeli (750-800) and Passage (720-960), followed by the plants of Machala and Santa Rosa, In regards to the processing of pigs the plant located in Machala were the highest (1,600), followed by Pasaje Santa Rosa and Marcabeli. Additionally, the tax rate cost was analyzed and the meat processing plants of Marcabeli had the largest value in comparison to Machala which had a lower rate. Finally, in regards to physical infrastructure, 87% of the 47 meat processing plants consulted were not up to code with building, maintenance and equipment regulations for efficient handling of meat, offal, inedible products and forfeited, etc. The type of meat processing plants in Marcabeli, Machala was mechanical i.e. chains attacked to hooks that held the meat in the air were the method of transport around the plant. In the meat processing plants of Santa Rosa and Pasaje the type of slaughtering is manual. Sixty nine percent of employee and related personnel respondents stated that they felt the distribution of area and space was not adequate working conditions. Thirty-one percent said that the area and spacing conditions were appropriate in Marcabeli and Pasaje. Furthermore, 57% of 31 participants asserted that the facilities felt unsafe and that there was not system to prevent work accidents; however 43% state that Machala and Pasaje meat processing plants were safe. The floors and ceilings of all meat processing plants were equipped with the statutory falls for waste disposal and rain water. When the participants were consulted on health technical management: 89% of all the plants stated that they had basic services to ensure the normal operation of the meat processing plants, seventy-four percent said it does not apply and that the industrial safety protocols were not mandatory to follow; not demanded. One hundred percent reported that ante-mortem inspection was not performed. Seventy four percent said that female meat was processed even in an advanced state of pregnancy. Additional result: Meat not hung in airing (85%) as should but the indicated standards. Compliance with animal health programs were not reviewed (72%). The meat was not transported under hygienic consumer market conditions (73%). Recoverable by-products such as blood, manure and rumen contents were exploited as only 14 % was used. Chubs and skin were not marketed. Pollution was a serious problem, 64% of the production yield was directed into channels that led to natural watersheds. Twenty-five percent opened into pits and 11% discharged directly to the sewer without any treatment. When the environmental impact was analyzed within and outside of the meat processing plants. Many did not comply with the law as were specified by the city and did not follow sanitation protocol. Unfortunately, there have been not studies on the presence of rodents and birds of prey. Finally, in relation to good operating practices, the staff was not identified according to their job role, did not have a contingency plan for the safety of personnel, (excluding Machala, however, which had a preliminary one), and no training or dissemination of laws and regulations to the staff. The improvement plan: The plan’s main focus is towards improving the documented poor conditions, which were compiled from the survey’s and interviews. The plan’s additional focus is towards decentralizing the meat processing plants from the government. The following are the areas that will be worked on: create a management system for the technical equipment and sanitation, create different ways to eliminate waste from the meat processing plants, compile information on the plant’s environmental impact based on it’s location, and foster better operation practices.